Combined Exploitation of Offshore Wind and Wave Energy in the Italian Seas: A Spatial Planning Approach - Azzellino, Arianna; Lanfredi, Caterina; Riefolo, Luigia; De Santis, Valentina; Contestabile, Pasquale; Vicinanza, Diego (Frontiers in Energy Research, 2019)
The opportunity to co-locate wind and wave energy exploitation is analysed in the Italian seas grounding on the rationale that benefits are greater when un-correlated resources are combined. The study shows that, although waves and winds are generally strongly correlated, in some conditions their correlation is lower and the combined energy harvesting more interesting. As spatial conflicts of sea use and demand for maritime space are increasingly growing, the development of the marine renewable energy sector needs to be evaluated in the perspective of the complex framework of existing uses, pressures and foresees developments. The early prediction of the areas of potential conflicts creates in fact the ground for mitigation actions or early negotiations between stakeholders. In this study the opportunity of co-locating offshore wind turbines and wave energy converters is analysed through a spatial planning approach. Both the potential for combining different renewable technologies, and the impact associated to such development was considered in the context of the existing pressures (e.g. naval traffic; mariculture activities; submarine cables routes; dredg spoils dumping; offshore activities; windfarms and ocean energy projects) and vulnerabilities (Marine Protected Areas, Key habitat presence) through quantitative indicators. The western coast off Sardinia island, the southern areas of Pantelleria island and the Tunisian coastal waters appear to be the most suitable sites. The study shows how quantitative spatial planning methods may support the selection of the sites of potential interest for the marine renewable energy sector in the perspective of cost-effectiveness and environmental impact minimization.